2009
DOI: 10.1590/s1415-47572009005000081
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of sigmodontine rodents (Cricetidae) along an altitudinal gradient of the Atlantic Rain Forest in southern Brazil

Abstract: The population genetic structure of two sympatric species of sigmodontine rodents (Oligoryzomys nigripes and Euryoryzomys russatus) was examined for mitochondrial DNA (mtDNA) sequence haplotypes of the control region. Samples were taken from three localities in the Atlantic Rain Forest in southern Brazil, along an altitudinal gradient with different types of habitat. In both species there was no genetic structure throughout their distribution, although levels of genetic variability and gene flow were high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
0
6
0
4
Order By: Relevance
“…Studies on O. nigripes genetic structure in an altitudinal range of about 750 m a.s.l. in southern Brazil showed high polymorphism and high levels of gene flow among populations occupying different types of habitat (Gonçalves, Marinho & Freitas, 2009). Cytogenetic analyses in specimens of O. nigripes from Paraguay, Argentina, and Brazil revealed a similar karyotype (2n = 62/FN = 78-82) (Myers & Carleton, 1981;Espinosa & Reig, 1991;Paresque et al, 2007).…”
Section: Reservoirs Of Hantavirus Genotypesmentioning
confidence: 99%
“…Studies on O. nigripes genetic structure in an altitudinal range of about 750 m a.s.l. in southern Brazil showed high polymorphism and high levels of gene flow among populations occupying different types of habitat (Gonçalves, Marinho & Freitas, 2009). Cytogenetic analyses in specimens of O. nigripes from Paraguay, Argentina, and Brazil revealed a similar karyotype (2n = 62/FN = 78-82) (Myers & Carleton, 1981;Espinosa & Reig, 1991;Paresque et al, 2007).…”
Section: Reservoirs Of Hantavirus Genotypesmentioning
confidence: 99%
“…Nonetheless, this number is likely an underestimate given that distinct studies have revealed candidate species that are pending of taxonomic revision (da Cruz & Weksler, ; Firth et al, ; Hanson, Utrera, & Fulhorst, ; Miranda et al, ; Palma et al, ; Rivera et al, ; Rogers et al, ; Teta, Jayat, Ortiz, & D'Elía, ). At the same time, only few species have been explored phylogeographically (e.g., O. longicaudatus , O. flavescens , O. microtis , O. nigripes ; Gonçalves, Marinho, & Freitas, ; Patton, Da Silva, & Malcolm, ; Palma et al, ; Rivera et al, ), which constitutes a first proxy of their variation; in fact, some species have not been studied since their original description (e.g., O. andinus , O. arenalis , O. destructor , O. griseolus ; Weksler & Bonvicino, ), at the time that some forms have controversial taxonomic status (e.g., O. fornesi , O. magellanicus , O. flavescens occidentalis ; Palma & Rodríguez‐Serrano, ; Rivera et al, ; Weksler, Lemos, D'Andrea, & Bonvicino, ).…”
Section: Introductionmentioning
confidence: 99%
“…O padrão encontrado para a rede de haplótipos é compatível com populações em expansão. A alta Hd e baixa π sugerem que a população seja composta por muitos haplótipos relacionados (Gonçalves et al, 2009) Foi possível observar que as populações de E. russatus não estão estruturadas, pois a variação encontrada dentro dos grupos é muito maior do que entre os grupos e a diferenciação encontrada entre os grupos A e C em relação aos demais deve ser decorrente de um processo de distanciamento geográfico (Gonçalves et al, 2009), no qual populações mais próximas tendem a ser geneticamente similares do que as que estão mais distantes (Paresque, 2010). Esses resultados auxiliam na compreensão da dinâmica da distribuição das espécies e são ferramentas importantes na área de gestão ambiental (Patton et al, 1996;.…”
Section: Análises Filogenéticasunclassified
“…Provavelmente, E. russatus não responde a modelos de diversificação baseados em rios ou montanhas, como ocorre para outros grupos de animais (Pellegrino et al, 2005;Ventura et al, 2012), e parece estar mais associada a eventos vicariantes recentes e isolamento por distância relacionados à dinâmica da MA (Ditchfield, 2000). Isso já havia sido evidenciado por Gonçalves et al (2009), que não encontraram estruturação populacional ao longo de um gradiente altitudinal para Euryoryzomys russatus. Entretanto, não deve ser um fenômeno generalizado para todos os roedores, uma vez que pode ocorrer em alguns casos, por exemplo, Delomys collinus (Bonvicino e Geise, 1995) e Blarinomys (Ventura et al, 2012).…”
Section: Análises Filogenéticasunclassified
See 1 more Smart Citation